The life cycle of the potentially zoonotic trematode Metagonimus romanicus (Digenea: Heterophyidae): New insights from published and original data - Mikuláš Oros; Miroslava Soldánová; Daniel Barčák; Petra Kundid; Caroline Jepkorir Kibet; Roman Kuchta; Martina Orosová; Tomáš Scholz (Food and Waterborne Parasitology, 2025)
Fish-borne zoonoses are emerging worldwide, and although most human cases remain confined to tropical regions, particularly Southeast and East Asia, a few cases have been reported in Europe. This review summarizes published and new data on the life cycle of Metagonimus romanicus (misidentified as M. yokogawai, a human pathogen common in East Asia), a heterophyid trematode and one of the potentially fish-borne parasites in Europe. Metagonimus romanicus is distributed from the middle Danube in Central Europe (Slovakia) to eastern Ukraine (including the rivers of the Black Sea basin). Its distribution area coincides with that of its first intermediate hosts, the melanopsid snails Microcolpia daudebartii acicularis and Esperiana esperi. While M. romanicus most likely has a strict specificity for its first snail hosts, metacercariae are generalists and have been detected in over 50 freshwater fish species from 18 families, especially leuciscids. Despite its wide distribution and frequent occurrence in freshwater fish, the zoonotic potential of M. romanicus appears to be low. This is probably due to the exclusive localization of the metacercariae in the fish scales rather than musculature, as well as the rare consumption of raw or undercooked fish in Europe. However, some risk remains and a small number of undiagnosed human infections due to accidental ingestion of scales during the preparation and cleaning of fish cannot be ruled out.